Trakasserier och kränkande särbehandling på arbetsplatsen - En studie av arbetsgivarens ansvar och sanktionssystemet vid överträdelser - Wassberg Christensen,Ida; Tideman,Kristina (2015)
Mental health issues in the workplace caused by harassment and bullying, is a widespread problem in today's society. Here we investigate the obligations of the employer when such problems occur. Mandatory rules concerning what the employer’s obligation in such cases are found both in civil law and administrative law. If they have led to crimes committed by the employer, rules on criminal matters in the Penal Code may be considered. For a behaviour to be classified as harassment under the Discrimination Act, the behaviour must be related to one of the seven grounds of discrimination or be of sexual nature. Bullying that is not related to discrimination is regulated in the Work Environment Act, which contains rules that require the employer to work for a good work environment. The employer's responsibility in preventing such problems is far-reaching when it comes to psychosocial health in the workplace. However, this responsibility is seldom exacted in practice, which may be a consequence of an imprecise regulation. We find no part of the law applicable to victims of bullying that is not classed as harassment. We miss an effective system for the victim's right to redress and his or her possibility of financial compensation.
Keywords: Trakasserier; Sexuella trakasserier; Kränkande särbehandling; Sanktioner; Arbetsmiljö; Harassment; Sexual harassment; Victimization; Sanctions; Working environment.